Complex pathological fracture and severe bone disease as a presenting manifestation of multiple myeloma: a case report - Sharma, Vishnu; Modi, Naman; Bagrodia, Vansh (International Journal of Research in Medical Sciences, 2023)
Multiple myeloma is a clonal plasma cell disorder that commonly affect bones, leading to characteristic bone findings on imaging studies. Here, we present the case of a male patient in his late-forties who presented with back pain and was found to have lytic lesions in skull and pelvis on X-ray. Further workup confirmed the diagnosis of Multiple myeloma and the patient was started on chemotherapy and denosumab. This case highlights the importance of early recognition of characteristic bone findings on imaging studies and conducting a thorough workup in patients with suspected multiple myeloma.